2019
DOI: 10.4236/ajibm.2019.91001
|View full text |Cite
|
Sign up to set email alerts
|

Research on Customer Geographic Proximity and Inventory Management—Empirical Evidence from Chinese Manufacturing Listed Companies

Abstract: Using the hand collected data of the top five clients of manufacturing enterprises in China, this paper examines the effect of customer geographic proximity on the inventory management level of manufacturing enterprises. The results show that there is a positive relation between the geographic proximity and inventory management level: the greater the geography proximity of customers, the lower the proportion of inventory, the higher the inventory turnover rate. This paper not only contributes to the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The findings revealed that the greater the adherence to inventory control, the greater the enterprises in consideration enjoyed higher competitive edge as well as a performance of the firm Furthermore, it was discovered that the enterprises' competitive edge had a favorable impact on their profitability. Kimaiyo and Ochiri's (2014) study concerned Kenyan manufacturing firm's inventory management and performance similar to Ngumi's (2015), Hu (2019) and Naliaka and Namusonge's (2015) studies. However, this study was concerned with the manner in which the cost reduction aspect of IM affected the functioning of these manufacturing firms; how inventory control systems affected their performance; how lead time affected their performance; and how supplier demand affected their performance.…”
Section: Inventory Management On the Market Performancementioning
confidence: 94%
“…The findings revealed that the greater the adherence to inventory control, the greater the enterprises in consideration enjoyed higher competitive edge as well as a performance of the firm Furthermore, it was discovered that the enterprises' competitive edge had a favorable impact on their profitability. Kimaiyo and Ochiri's (2014) study concerned Kenyan manufacturing firm's inventory management and performance similar to Ngumi's (2015), Hu (2019) and Naliaka and Namusonge's (2015) studies. However, this study was concerned with the manner in which the cost reduction aspect of IM affected the functioning of these manufacturing firms; how inventory control systems affected their performance; how lead time affected their performance; and how supplier demand affected their performance.…”
Section: Inventory Management On the Market Performancementioning
confidence: 94%